Cornered at a Bar: How Victim Clothing, Alcohol Intake, and Relationship With Bystander Impact Intention to Help. (August 2019) - Zelin, Alexandra I.; Walker, Ruth V.; Johnson, Dawn M.
While a negative relationship between rape myth acceptance (RMA) and bystander behavior is established, the specific myths associated with bystander behavior are not well understood. In Study 1, we presented 260 participants with vignettes manipulating clothing and alcohol intake of a woman victim to see how it affected intention to help. In Study 2, we presented 247 participants with similar vignettes, manipulating alcohol intake and relationship with the bystander. Contrary to previous research on RMA, participants were significantly more willing to intervene if the woman was intoxicated. Intervention also depended upon the participants' relationship to the woman: stranger or acquaintance.